PERKEMBANGAN KARAKTER HADES DALAM NOVEL HAVE A HOT TIME, HADES! KARYA KATE MCMULLAN (ANALISIS PSIKOLOGI) - JASTIN, CRISANDI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â Â ThisÂ researchÂ isÂ entitledÂ â€œPerkembanganÂ KarakterÂ HadesÂ DalamÂ NovelÂ Have aÂ HotÂ Time,Â Hades!Â KaryaÂ KateÂ McMullanÂ (AnalisisÂ Psikologi)â€.Â TheÂ aimsÂ ofÂ thisÂ researchÂ isÂ toÂ identifyÂ andÂ analyzeÂ theÂ stagesÂ ofÂ characterÂ developmentÂ ofÂ HadesÂ fromÂ psychologicalÂ perspective,Â asÂ wellÂ asÂ toÂ analyzeÂ theÂ characterÂ ofÂ HadesÂ himself. Â InÂ termsÂ ofÂ methodology,Â theÂ theoryÂ usedÂ forÂ thisÂ analysisÂ isÂ the psychosocialÂ developmentÂ theoryÂ byÂ ErikÂ EriksonÂ inÂ ChildhoodÂ andÂ Society (1950).Â ThisÂ researchÂ alsoÂ appliedÂ theÂ combinationÂ ofÂ twoÂ approachesÂ namelyÂ theÂ intrinsicÂ andÂ extrinsicÂ approaches. Â TheÂ resultÂ ofÂ thisÂ researchÂ showsÂ thatÂ HadesÂ inÂ theÂ novelÂ Have aÂ HotÂ Time,Â Hades!Â Â haveÂ aÂ uniqueÂ andÂ differentÂ personalityÂ thanÂ theÂ HadesÂ generallyÂ knownÂ fromÂ otherÂ literaryÂ works. TheyÂ are,Â critics,Â sarcastic,Â criticalÂ thinking,Â positiveÂ thinking,Â andÂ compassionate.Â WhileÂ theÂ stagesÂ ofÂ psychosocialÂ developmentÂ ofÂ HadesÂ thatÂ areÂ presentÂ inÂ theÂ novelÂ areÂ Trust vs. Mistrust,Â Autonomy vs. Shame and Doubt,Â Initiative vs. Guilt,Â Industry vs. Inferiority,Â Identity vs. Confusion, Intimacy vs. Isolation,Â andÂ showsÂ theÂ resultÂ ofÂ HadesÂ passÂ allÂ theÂ stagesÂ presentÂ withÂ theÂ dominationÂ ofÂ positiveÂ outcome.Â Â Â Â ___________________________________________________________ Keywords:Â characterÂ development,Â psychologicalÂ analysis,Â Hades